A finite element method for evaluating a double integral arising from a Dirichlet problem in fluid mechanics - SHIVAKUMAR, P. N.; YAN, NINGNING; JI, CHUANXIANG (Communications in numerical methods in engineering, 1997)
In this paper we give a finite element method and its error estimate for evaluating double integrals over a smooth domain. The results are used to compare rates of flow of a viscous incompressible fluid in a pipe‐in‐pipe system with different doubly connected cross‐sections. These numerical results confirm an earlier conjecture regarding the rates of flow. ©1997 John Wiley & Sons, Ltd.